Pemberian NAA (Naphthalene Acetic Acid) dan BAP (Benzil Amino Purine) dalam Inisiasi Petal Krisan (Chrysanthemum indicum L.) Terhadap Pertumbuhan Organogenesis Tunas Secara In Vitro pada Media MS (Murashige and Skoog) - Fuji Syahidah Fauziah; Sulistyo Sidik Purnomo; Nurcahyo Widyodaru Saputro; Ronald Bunga Mayang (Jurnal Ilmiah Wahana Pendidikan, 2021)
The research was carried out at Laboratorium Pemuliaan Terpadu, precisely at Laboratorium Konservasi Balai Penelitian Tanaman Hias Kebun Percobaan Segunung, Pacet, Cianjur from March to June 2021. The Research Method uses experimental methods with non-parametric statistics with 12 treatments and 5 repeats. Perlakuan NAA dengan konsentrasi 0,1 ppm; 0,2 ppm; dan BAP yaitu konsentrasi 0,5 ppm; 1 ppm; dan 1,5 ppm. The results of the observations were analyzed descriptively using the Wallis Kruskal Test. Based on several observed variables, the results showed different results in the degree of significance between the explants in NAA and BAP administration, in callus diameter variables showed significant different results, while in variables the number and height of the shoots showed significantly different results. The results of the study showed NAA and BAP concentrations on A2B3 treatment (concentration 0.1 ppm NAA+1 ppm BAP) were able to produce the best shoots against the number of shoots. In A3B3 treatment (concentration 0.2 ppm NAA + 1 ppm BAP) is capable of producing the best shoot against the height of the shoot.